Beiträge zur Forschungen Lausitzer Brauchtums - Dąbrowski, Jan (Institute of Archaeology Rzeszów University, 2013)
This article is devoted to pottery vessels or their small sets from cemeteries, which do not contain the remains of the deceased and do not repeat the typical inventories for grave goods. These features include small vessels, usually containers for liquids, and rarely other items. A few chemical analyses have shown that they may have contained food. Unfortunately, descriptions of materials from outside graves are often incomplete and, therefore, there is no doubt that the known catalogue only contains some of the discovered artefacts. Nevertheless there are 273 features from 62 cemeteries. These mostly contain one vessel (up to a maximum of seven items) amounting from 0.2 to 5.8 % of the features from large cemeteries. It should be noted that as for the Lusatian cemeteries there are often metal, stone and flint artefacts among the graves. On the other hand, hoards of vessels are rare. The nature of these vessels suggests that they may have been used for ritual libations, which is considered to be common then. However, it appears that the offerings were given during rituals, which were not always associated with the funeral.
Przyczynki do badania obrzędowości kultury łużyckiej
Keywords: Lusatian culture; Bronze Age; Early Iron Age; funeral rites; offerings; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology